2021
DOI: 10.3390/nu13020315
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Healthy Lifestyle Behaviors with Overweight and Obesity among Older Adults from 21 Countries

Abstract: This study aimed to analyze the association of healthy lifestyle behaviors with overweight and obesity among Europeans aged 65+ years. Data were from the 2014 European Social Survey, analyzing 21 countries. Five lifestyle behaviors (physical activity, fruit and vegetable consumption, sleep quality, drinking alcohol, and smoking) were analyzed. Binary logistic regressions were performed. A total of 8938 participants (4099 men) 65 years and older, mean age—73.6 (SD: 6.6) presented prevalence of overweight of 42.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 42 publications
(59 reference statements)
1
11
1
Order By: Relevance
“…In any case, the nutritional status of our community-dwelling older persons was very good (only 1.2% malnutrition), but the presence of obesity was high compared to previous reports. Thus, a study of older adults in 21 European countries reported only 20.9% obesity compared to 45.6% in our sample population [51]. Among other causes, this high prevalence could be due to a certain north-south gradient.…”
Section: Discussioncontrasting
confidence: 60%
“…In any case, the nutritional status of our community-dwelling older persons was very good (only 1.2% malnutrition), but the presence of obesity was high compared to previous reports. Thus, a study of older adults in 21 European countries reported only 20.9% obesity compared to 45.6% in our sample population [51]. Among other causes, this high prevalence could be due to a certain north-south gradient.…”
Section: Discussioncontrasting
confidence: 60%
“…The leading causes of the increase in obesity and overweight in the Eastern Mediterranean (EMRO) are lifestyle changes, including unhealthy eating habits, physical inactivity, and cultural, social, and economic changes [ 5 , 6 ]. On the other hand, using a plant-based diet and physical activity in daily life reduces the risk of obesity [ 7 ]. Kuwait, Qatar, and Libya, the three EMRO countries, were among the top ten countries with the highest prevalence of obesity in the world in 2013 [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…22 A multicohort study conducted with adults from 21 European countries reported that physical activity (5 days a week) was the most preventative health behavior and reduced the probability of obesity by 42%. 23 Physical activity requires energy expenditure above the basal level. Even activities at this level repair the body, exercise, which is defined as planned structured movements performed at a certain intensity, facilitates coping with obesity.…”
Section: Discussionmentioning
confidence: 99%